A study on Maruca vitrata infestation of Yard-long beans (Vigna unguiculata subspecies sesquipedalis). Issue 1 (September 2015) - Jayasinghe, R.C.; Premachandra, W.T.S. Dammini; Neilson, Roy
Abstract: Globally, Maruca vitrata (Geyer) is a serious yield constraint on food legumes including Yard-long bean ( Vigna unguiculata subspecies sesquipedalis ). However, there is a dearth of information on its damage potential, distribution and population dynamics in Yard-long beans. In the present study, the level of M. vitrata larval infestation on flowers and pods of Yard-long beans in Sri Lanka was determined with respect to three consecutive cropping seasons, Yala, Off and Maha. Results indicated that larval infestation and abundance varied with developmental stage of flowers and pods, cropping season and their combined interactive effects. Flowers of Yard-long beans were more prone to M. vitrata larval attack compared to pods. Abundance and level of infestation of M. vitrata varied with plant parts, having a ranking of flower buds (highest) > open flowers > mature pods > immature pods (lowest). Peak infestation was observed six and eight weeks after planting on flowers and pods, respectively. Among the three cropping seasons, M. vitrata infestation was found to be higher during Maha and Off seasons compared to Yala. The findings of this study contribute to the identified knowledge gap regarding the field biology of an acknowledged important pest, M. vitrata, in a previously understudied crop in Sri Lanka.